Biocompatible Cost-Effective Electrophysiological Monitoring with Oxidation-Free Cu–Au Core–Shell Nanowire - Kim, Dongkwan; Bang, Junhyuk; Won, Phillip; Kim, Youngtaek; Jung, Jinwook; Lee, Jinwoo; Kwon, Jinhyeong; Lee, Habeom; Hong, Sukjoon; Jeon, Noo Li; Han, Seungyong; Ko, Seung Hwan (Advanced Materials Technologies, 2020)
In spite of its excellent electrical, mechanical, and low-cost characteristics, copper nanowire has fatal issues in the oxidation problem and the lack of biological compatibility, which occasionally outweighs its advantages and limits its usage as electronics or biodevice applications. In this study, a novel wet chemical synthesis method is developed for the oxidation-free Cu–Au core–shell nanowire based on the prepared Cu nanowire with alkylamine-mediated synthesis and ligand exchange. The synthesized Cu–Au core–shell nanowire exhibits improved electrical stability against thermal oxidation under the harsh environment of 80 °C and 80% relative humidity. Additionally, to substantiate suitability for the biomedical application, the enhanced chemical stability and biocompatibility are investigated by utilizing the artificial perspiration and the cell culture. As a proof-of-concept demonstration, high performance wearable electromyogram (EMG), electrocardiogram (ECG) sensors for electrophysiological monitoring with the Cu–Au core–shell nanowire electrode are demonstrated with superior oxidation-resistance and biocompatibility even after the harsh environment test. The Cu–Au core–shell nanowire can provide promising, cost-effective electrode materials for various wearable electronics applications.
Keywords: Biological compatibility; Biomedical applications; Electrical stability; Electrocardiogram (ECG) sensors; Electrode material; Electronics applications; Nanowire electrodes; Wet chemical synthesis; copper nanowires; core–shell nanowires; Cu–Au nanowires; electrocardiography sensors; electromyogram sensors; ligand exchange; wearable electronics